Leucaena leucocephala (Subabul) as an Economic Pulp Wood - Agrawal, Anupam; Garg, S. C.; Misra, Prabhat; Jafri, S. H. H. (Indian Forester, 1985)
There is imperative need for the nation to search for new species which could fill the ever widening gap due to rapid dwindling of forest and increasing demand for pulp, fuel and timber wood. In this context Leucaena leucocephala, leguminous tree from tropical America, commonly called Subabul, has emerged as wonder tree since the last few years, because of its fast growth and good yield. It is a good wood for pulping, fuel and timber. It has many additional advantages, such as increasing of the soil fertility, water conservation etc. It also provides seeds for industrial use and is a good fodder for domestic animals. For experimental purpose trial plantation under varied conditions of irrigation of different species were taken. Out of these, Subabul has shown the best results. For pulp and paper industries it is an excellent raw material with high yield. A scheme for large scale plantation of Subabul covering the economics of working is suggested in this article.